PKM PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS CHATGPT DI SMKN 6 TAKALAR - Hardi, Hardi; Khadafi, Muhammad; Hasryif, Hasryif; Susanto, Cucut; Nurdiansah, Nurdiansah (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
Community Service Research is intended as a form of approach offered to overcome the problems that exist at SMKN 6 Takalar. The problem that is often faced by teachers at SMKN 6 Takalar is in the process of teaching students. The ability of teachers to search for teaching materials using the GPT Chat (Generative Pre-Trained Transformer) application is currently still not used, especially by teachers at SMAN 6 Barru, due to limited knowledge in managing it to teach students. Training in creating AI (Artificial Intelligence) based teaching materials as a means of transferring subjects using the ChatGPT application. This learning media is an activity to optimize teaching and learning for students at SMKN 6 Takalar. With the current acceleration of technological development, if a teacher still uses teaching techniques manually, it will be left behind and boring for a student. Without training activities that are constructive in nature for both personal and group interests, it will result in lagging behind in utilizing animation media as a means for teaching. From the PKM training on AI-based learning media (ChatGPT) at SMKN 6 Takalar, it can be concluded that providing an Introduction to Learning Media and an Introduction to ChatGPT along with other tools is very effective and successful. Meanwhile, for practical activities: Making learning materials for each participant according to their lesson and determining the target students being taught so they can understand the lesson. All the activities trained have gone well and really helped the learning and teaching of SMKN 6 Takalar teachers